PENGARUH MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN MINDMAPPING TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK PADA PEMBELAJARAN BIOLOGI SMA - Wulandari, Dini Busfi; Helendra; Yogica, Relsas; Fajrina, Suci (Jurnal Biogenerasi, 2024)
The purpose of this study is to see if there is an effect of the Problem Based Learning (PBL) model assisted by mindmapping on the critical thinking skills of students in high school biology learning. This research is quasi experiment with a two group pretest-posttest design. The population in this study were all E phase students of SMAN 1 Timpeh in the 2023/2024 school year which amounted to 124 people consisting of 4 classes. Furthermore, the determination of the sample to be used as an experimental class and control class using purposive sampling technique. Data collection techniques used in this study were tests. The test used in this study was a test of students' critical thinking skills through pretest and posttest. Data analysis activities consist of data processing and statistical analysis activities. The results showed that the Problem Based Learning (PBL) model assisted by mindmapping had a positive effect on the critical thinking skills of students in high school biology learning, where the results of hypothesis testing using the independent sample t-test showed that the significance (2-tailed) was 0.000 which means <0.05 and the average value of critical thinking skills based on pretest and posttest scores in the experimental class increased by 23.4%.